2014
DOI: 10.12659/ajcr.890166
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal tumoral calcinosis in a 4-year-old girl

Abstract: Patient: Female, 4Final Diagnosis: Tumoral calcinosisSymptoms: Hard immobile massMedication: —Clinical Procedure: —Specialty: SurgeryObjective:Congenital defectsBackground:Tumoral calcinosis is an uncommon condition associated with the deposition of painless calcific masses. It is more common in childhood or early adolescence of African-American females.Case Report:We present a case of a 4-year-old girl with tumoral calcinosis treated surgically. The case is rather rare in terms of the age of the patient and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Calcium deposits were found within the KA lesions, such a pattern being unique. To the best of our knowledge, there is only one report of KA with secondary ossification in the literature,[ 9 ] and our case happens to be the second case where calcium salt deposition is found within the KA lesions.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Calcium deposits were found within the KA lesions, such a pattern being unique. To the best of our knowledge, there is only one report of KA with secondary ossification in the literature,[ 9 ] and our case happens to be the second case where calcium salt deposition is found within the KA lesions.…”
Section: Discussionmentioning
confidence: 72%
“…Tumoral calcinosis (TC), a distinct clinico-histological entity, is a form of idiopathic calcinosis cutis, which is characterized by tumor-like periarticular deposits of calcium, mainly found in the regions of hip, shoulder, elbow, and other pressure points, rarely affecting distal locations such as the hands and feet. [ 8 ] Mostly, it affects young adults, but it can occur as early as 4 years of age,[ 9 ] the present patient being 13 years old. Although the exact cause is unknown, a pathogenesis-based classification has subdivided this entity into three types: (1) primary normo-phosphatemic tumoral calcinosis (NPTC), (2) primary hyperphosphatemic tumoral calcinosis, and (3) secondary tumoral calcinosis, characterized by the presence of underlying disorders.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are different literatures describing the efficacy of medical and surgical treatment in tumoral calcinosis in children. Sayar et al [8] reported in his study of a four-year-old girl who presented to the pediatric surgery clinic due to swelling on the left gluteal region for three months. She had no history of trauma or infection.…”
Section: Discussionmentioning
confidence: 99%